Application of organoid models in colorectal cancer research - Zhi-Li LI; Lu WANG; Yu-Ting WANG; Chu-Yue HUANG; An-Qi WANG; Zheng-Rong LYU; Zhi-Min FAN (Yixue xinzhi zazhi)
Organoid is a new research tool that has gradually emerged in recent years. They promise to have a broad application prospect in the fields of disease development, drug screening, new drug development, per-sonalized medicine and other fields. Nowadays, the colorectal cancer organoid model has become relatively mature. This paper reviews the common models in colorectal cancer research and the construction and applica-tion of colorectal cancer organoids.